Identifying abolitionist alignments in community psychology: A path toward transformation. - DaViera, Andrea L.; Bailey, Caroline; Lakind, Davielle; Kivell, Natalie; Areguy, Fitsum; Byrd, Kymberly (American Journal of Community Psychology, 2024)
Psychology is grounded in the ethical principles of beneficence and nonmaleficence, that is, "do no harm." Yet many have argued that psychology as a field is attached to carceral systems and ideologies that uphold the prison industrial complex (PIC), including the field of community psychology (CP). There have been recent calls in other areas of psychology to transform the discipline into an abolitionist social science, but this discourse is nascent in CP. This paper uses the semantic device of "algorithms" (e.g., conventions to guide thinking and decision‐making) to identify the areas of alignment and misalignment between abolition and CP in the service of moving us toward greater alignment. The authors propose that many in CP are already oriented to abolition because of our values and theories of empowerment, promotion, and systems change; our areas of misalignment between abolition and CP hold the potential to evolve. We conclude with proposing implications for the field of CP, including commitments to the belief that (1) the PIC cannot be reformed, and (2) abolition must be aligned with other transnational liberation efforts (e.g., decolonization). Highlights: The prison industrial complex (PIC) is a White supremacist system of violence that needs to be abolished.PIC abolition would replace systems of punishment and control with care and accountability.Community psychology (CP) and abolition are aligned in commitments to social justice and systems change.CP and abolition have misalignments, but they can be shifted.Aligning with abolition will help CP follow the "decolonial turn" for which many are calling.